2013
DOI: 10.1371/journal.pone.0067478
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Resting-State Activities and Functional Connectivities of the Anterior and the Posterior Cortexes in Medication-Naïve Patients with Obsessive-Compulsive Disorder

Abstract: BackgroundObsessive-compulsive disorder (OCD) is a mental illness characterized by the loss of control. Because the cingulate cortex is believed to be important in executive functions, such as inhibition, we used functional magnetic resonance imaging (fMRI) techniques to examine whether and how activity and functional connectivity (FC) of the cingulate cortex were altered in drug-naïve OCD patients.MethodsTwenty-three medication-naïve OCD patients and 23 well-matched healthy controls received fMRI scans in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 44 publications
3
51
0
Order By: Relevance
“…Formerly, decreased coactivation in certain resting-state networks has been linked to Alzheimer disease, 36 obsessive-compulsive disorder, 37 and cocaine addiction, 38 and increased coactivation in certain resting-state networks has been linked to better performances in response inhibition 21 and motor skill learning. 39 In these studies, the extent of coactivation was deemed to represent the strength of functional interactions between the regions within the networks.…”
Section: Discussionmentioning
confidence: 99%
“…Formerly, decreased coactivation in certain resting-state networks has been linked to Alzheimer disease, 36 obsessive-compulsive disorder, 37 and cocaine addiction, 38 and increased coactivation in certain resting-state networks has been linked to better performances in response inhibition 21 and motor skill learning. 39 In these studies, the extent of coactivation was deemed to represent the strength of functional interactions between the regions within the networks.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with an overactive error control system in OCD subserving suppression of prepotent responses during decision-making. Several studies of FC connectivity confirmed alteration in the fronto-striato-thalamo-cortical (i.e., [199][200][201][202][203][204][205][206][207]). The dysregulation of the fronto-striato-thalamo-cortical circuit may be one of the major findings, which can help to differentiate the two disorders, as the presence of an increased WM integrity during in pediatric and adolescent patients affected by OCD.…”
Section: Developmental Perspectivementioning
confidence: 95%
“…These include reductions in gray matter (Radua and Mataix-Cols 2009; Rotge and others 2009), hyperactivity at rest (Maia and others 2008), increased activation during symptom provocation (Maia and others 2008), and increased activation during conflict monitoring (Del Casale and others 2011). More recent studies have characterized abnormalities in OCD patients in ACC functional connectivity (Cheng and others 2013; Cocchi and others 2012; Fitzgerald and others 2011; Gruner and others 2014; Hou and others 2012; Posner and others 2013; Yang and others 2010) and integrity of the associated white matter of the cingulum bundle (Cannistraro and others 2007; Gruner and others 2012; Koch and others 2014; Szeszko and others 2005). …”
Section: Abnormal Arbitration In Ocd?mentioning
confidence: 99%